2001
DOI: 10.1002/fam.758
|View full text |Cite
|
Sign up to set email alerts
|

Durability of fire retardant treated wood products at humid and exterior conditions review of literature

Abstract: Fire retardants may considerably improve the 5re properties of wood products, but the durability, e.g. in exterior applications, has not been addressed fully. This paper reviews the existing knowledge and experience mainly from the USA with the aim of supporting further development in Europe. The review is concentrated on pressure impregnated 5re retardant treated wood products which have the best opportunities for increased durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 9 publications
1
34
0
1
Order By: Relevance
“…Wood materials could be impregnated with inorganic salts to improve their flame retarding properties [1][2][3]. After diffusion into the material they must be transformed into water-insoluble compounds to prevent the salt-washing.…”
Section: Introductionmentioning
confidence: 99%
“…Wood materials could be impregnated with inorganic salts to improve their flame retarding properties [1][2][3]. After diffusion into the material they must be transformed into water-insoluble compounds to prevent the salt-washing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have reported that wood and wood-based panels treated with inorganic salts, such as boron compounds or phosphates, increase their hygroscopicity, particularly at high RHs (Dundar et al 2009;Candan et al 2011). Increases in the MC between 2% and 16% at a high RH have been reported for wood-based panels in several studies (Holmes 1977;Östman et al 2001;Dundar et al 2009;Candan et al 2011). The increase of water adsorption could be attributed to the new adsorption sites that were formed by the treatment.…”
Section: Moisture Content Changes Of the Sandwich Panelsmentioning
confidence: 88%
“…A US study on exterior exposure of North American products during ten years [1] and a literature review [2] have been published.…”
Section: Durability Classes For Fire Performance -Principles and Methodsmentioning
confidence: 99%